Cách 1 :
Ta có : 3n + 4 chia hết cho n - 1
=> 3n - 3 + 7 chia hết cho n - 1
=> 3(n - 1) + 7 chia hết cho n - 1
=> 7 chia hết cho n - 1
=> n - 1 thuộc Ư(7) = {-7;-1;1;7}
Ta có bảng :
n - 1 | -7 | -1 | 1 | 7 |
n | -6 | 0 | 2 | 8 |
Cách 2 :
Ta có : \(\frac{3n+4}{n-1}=\frac{3n-3+7}{n-1}=\frac{3\left(n-1\right)}{n-1}+\frac{7}{n-1}=3+\frac{7}{n-1}\)
Để 3n + 4 chia hết cho n - 1 thì 7 chia hết cho n - 1
=> 7 chia hết cho n - 1
=> n - 1 thuộc Ư(7) = {-7;-1;1;7}
Ta có bảng :
n - 1 | -7 | -1 | 1 | 7 |
n | -6 | 0 | 2 | 8 |
a)\(\frac{3n+4}{n-1}\)= \(\frac{3n-3+7}{n-1}\)= \(\frac{3.\left(n-1\right)}{n-1}\)+ \(\frac{7}{n+1}\)= \(3+\frac{7}{n-1}\)
Để \(3n+4\)\(⋮\)\(n-1\)thì \(n-1\)\(\in\)\(Ư\left(7\right)\)
Ta có bảng sau :
\(n-1\)\(1\) \(-1\) \(7\) \(-7\)
\(n\) \(2\) \(0\) \(8\) \(-6\).
Vậy \(n\)\(\in\)\([\)\(2\); \(0\); \(8\); \(-6\)\(]\).